2018
DOI: 10.3390/su10082856
|View full text |Cite
|
Sign up to set email alerts
|

Social and Personal Dimensions as Predictors of Sustainable Intention to Use Facebook in Korea: An Empirical Analysis

Abstract: Abstract:The purpose of this research is to investigate the role of social and personal dimensions in predicting sustainable intention to use a social networking site (SNS). We propose and test an integrative SNS acceptance model based on the theory of planned behavior (TPB), the technology acceptance model (TAM), and the social influence theory. Included in the model are the attitudes toward the use of a SNS, the subjective norm, prevalence of information cascades, and the perceived behavioral control as ante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 46 publications
(71 reference statements)
0
19
0
Order By: Relevance
“…It seems that there are empirical findings that have focused on the effects of PEU, PE, and PU on consumers' ATUSM. These relationships (e.g., the effects of PEU and PU on attitude) are also supported in the framework of TAM, e.g., [23,36,[41][42][43][44]. For example, Lee et al [10] reported that PE triggered consumers' attitude toward using Facebook for festival searches.…”
Section: Theoretical Focus and Hypothesesmentioning
confidence: 85%
“…It seems that there are empirical findings that have focused on the effects of PEU, PE, and PU on consumers' ATUSM. These relationships (e.g., the effects of PEU and PU on attitude) are also supported in the framework of TAM, e.g., [23,36,[41][42][43][44]. For example, Lee et al [10] reported that PE triggered consumers' attitude toward using Facebook for festival searches.…”
Section: Theoretical Focus and Hypothesesmentioning
confidence: 85%
“…It should be noted that the influence of perceptions and the power of the subjective norm is particularly relevant within the group of people whose influence contributes to maintaining perceptions and the subjective norm [110][111][112]. Such influence is more significant when there are favourable expectations regarding the attainment of benefits from entrepreneurship and when the subject possesses a high self-concept of an entrepreneur [113,114]. Therefore, the following hypothesis stipulates that: Hypothesis 5 (H5).…”
Section: Hypothesis 2 (H2)mentioning
confidence: 98%
“…The Theory of Reasoned Action, on the other hand, recognises the influence of social pressure on people’s perceptions (Ajzen and Fishbein, 1980; Hong, 2018; Otieno et al , 2016). Social pressure occurs because some individuals or groups are so important that they can influence other people’s attitudes towards an object.…”
Section: Theories Of Attitude Formation and Attitude Changementioning
confidence: 99%